Relationships between gender role, acculturation, conflict resolution and marital satisfaction among Iranian postgraduates in public universities in Malaysia - Ahangar, Katayoon (2017)
Marriage is a special relationship between two people in which its quality plays an important role in one’s life. Marital satisfaction is a personal perception and is strongly linked to the health and happiness of a marriage. This study investigates the relationships between conflict resolution, acculturation and marital satisfaction and the moderating role of gender role attitude on the relationship between the aforementioned factors among married Iranian students in Malaysian universities. Bronfenbrenner’ ecological model of human development, Berry’s acculturation theory, and gender role theory were utilized to provide a valid foundation for explaining relationships between gender role attitude, acculturation, conflict resolution and marital satisfaction among married Iranian students. In this study, a correlational research design has been employed. An online web survey technique employed 386 respondents aged between 25 and 56 years old that were made up of married Iranian postgraduate students studying in Malaysian public universities. The respondents completed the PREPARE/ENRICH Couple Satisfaction Scale (Olson, Larson and Olson, 2009), the PREPARE/ENRICH Conflict Resolution Scale (Olson, Larson and Olson, 2009), a slightly altered version of the Gender Role Attitude Scale (Prasad and Baron, 1996) and the East Asian Acculturation Measure (EAAM) (Barry, 2001) to measure the variables respectively. Partial Least Squares-Structural Equation Modeling was used to test the research hypotheses for this study. The results showed that acculturation and conflict resolution have a significant relationship with marital satisfaction. However, gender role attitude does not significantly moderate the relationship between the aforementioned variables and marital satisfaction. This study advances the understanding of the importance of conflict management and acculturation as influencing factors of marital satisfaction. It also increases the understanding on the importance of gender role attitude among married Iranian students. This supports the theory that better acculturation and conflict resolution leads to a higher level of marital satisfaction. The finding of this study may potentially be one of the relevant factors for intervention and prevention programs that deals with married Iranian students who are studying abroad, specifically in Malaysia. Acculturation and conflict management while managing various responsibilities as a married student in a foreign country is also important to highlight.